Extent and activity of adult hippocampal neurogenesis - Betters, Ryan K.; Manly, Robert W.; Huynh, Pearl M.; Tunc-Ozcan, Elif (Frontiers in Neuroscience, 2025)
Our understanding of adult neurogenesis has advanced far since Joseph Altman reported newborn neurons in the adult rodent brain over 60 years ago, but only recently have we been able to directly interrogate its role in the brain. While the olfactory-associated neurogenesis seen in the subventricular zone of many other mammals is greatly diminished in humans, hippocampal neurogenesis persists and may have important roles for learning, memory, and emotional regulation. A reduction in neurogenesis may play a role in neurodegenerative disease, and recent studies have suggested that hippocampal neurogenesis counteracts age-associated cognitive decline. Neurogenesis is also negatively impacted by chronic stress, a major contributor to a wide variety of psychiatric disorders. Interestingly, antidepressants have been shown to enhance neurogenesis, and some of their behavioral effects are driven by newborn neurons in the dentate gyrus of the hippocampus. Little is known, however, about how these newborn neurons integrate into and contribute to the neural circuitry of the hippocampus. Recent evidence suggests that the behavioral implications of neurogenesis are driven by the activity of newborn neurons, which may or may not be coupled to the extent of cell proliferation. This review discusses what is known about these two elements of neurogenesis, and how a complete picture of both is necessary to fully understand their physiological implications.